Tant qu’il y aura des « profanes »… dans la gestion des risques littoraux - Nicolas Rocle; Bruno Bouet; Silvère Chasseriaud; Sandrine Lyser (VertigO)
Governing practices in French coastal risk management still tend to prioritize expert knowledge in the taking of decisions. Indeed, this policy domain persistently depends upon settled assumptions that local citizens either lack knowledge about risk or are likely to reason on the basis of their emotions and in the short-term. Consequently, they are frequently excluded from decisional arenas making adaptation choices, such as coastal planned retreat. We argue that this kind of policy making rests upon what is called the “public deficit model” in the public understanding of science, and that this model is constantly renewed by some dominant actors despite participatory principles. Based on a questionnaire survey carried out with over 500 individuals (inhabitants, professionals and tourists) in Lacanau, Aquitaine coastline, during the summer of 2013, we found that, on the contrary, citizens have extensive knowledge about coastal erosion and associated issues. Moreover, their knowledge maps onto that held by scientists. Not only do they know about coastal erosion, but they can articulate their knowledge in synthetic ways and envisage long-term solutions to problems. Arguments for their exclusion based on lack of knowledge or perception biases cannot therefore be sustained. Our findings thus go towards removing one of the institutional obstacles blocking change towards participatory governance for risk management.